Study of studs shear connectors behaviour in composite beams with profiled steel sheeting - Jorge Douglas Bonilla Rocha (Revista de la Construcción, 2015)
This work presents an FE study concerning the prediction of the shear resistance of headed stud connectors in composite beams with profiled steel sheeting subjected to static load. To confirm the FE simulation for the determination of the shear resistance of stud connectors, many experimental push-out tests whose results are available in the literature were used as a database. The FE simulations took into account the influence of many physical and mechanical parameters that affect the shear resistance of the stud connectors and such parameters are reported in the course of this paper. The prediction of the shear resistance of such studs is also calculated from currently used Standards, such as: AISC-LRFD and Eurocode-4. This research proposes new formulations for the prediction of the shear resistance and the results show that the proposed formulations significantly improve the prediction of the shear resistance of headed stud connectors subjected to static load.